Autonomic and trusted computing 8th International Conference, ATC 2011, Banff, Canada, September 2-4, 2011. Proceedings - Calero, Jose M. Alcaraz; Yang, Laurence T.; Marmol, Félix Gómez; Villalba, Luis Javier; Li, Andy Xiaolin; Wang, Yan (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Autonomic and Trusted Computing, ATC 2011, held in Banff, Canada, September 2011. The 17 revised full papers presented together with 1 keynote speech were carefully reviewed and selected from numerous submissions. The papers address all current issues in autonomic architectures, models and systems, autonomic communications, trusted and secure computing, reliable, secure and trust applicatio